A Synthesis of the Pseudopterosin A–F Aglycone - Cooksey, John P.; Kocieński, Philip J.; Schmidt, Arndt W.; Snaddon, Thomas N.; Kilner, Colin A. (Synthesis, 2012)
The synthesis of the pseudopterosin A–F aglycone from 3-methylcatechol features (a) the use of asymmetric Ireland–Claisen and aryl Claisen rearrangements to install three of the four stereocentres present in the molecule and (b) an A→AB→ABC annulation strategy using ring-closing metathesis and cationic cyclisation reactions as the key steps.
Keywords: total synthesis; terpenoids; ring closure; rearrangement; metathesis; pericyclic reaction